Bridging the gap: Analysis of systemic barriers to irrigation technology supply businesses in Ethiopia - Teferi, Ermias Tesfaye; Assefa, Tewodros T.; Tilahun, Seifu A.; Wassie, Solomon Bizuayehu; Minh, Thai Thi; Béné, Christophe (Elsevier, 2024)
This study examines the barriers faced by irrigation technology and service suppliers in Ethiopia, and their influence on business effectiveness. Data were collected from 42 firm owners and managers across 21 enterprises through online surveys, phone calls, and in-person interviews in August 2020. Additional insights were provided by 35 key informants. The study utilized a qualitative analysis of survey responses by employing narrative and triangulating information gathered from several actors in the irrigation technology supply chain. The results indicate that a range of barrier categories, including difficulties linked to business enablement, technology user behavior, and business capacity, significantly impede the development and success of small-scale irrigation technology enterprises in Ethiopia. More specifically, barriers include the increasing diffusion of substandard irrigation technology products, such as water lifting devices, and a scarcity of genuine spare parts, which present major obstacles for small-scale irrigation technology suppliers in Ethiopia. Insufficient user awareness regarding the importance of maintenance and repair services has led to frequent equipment failures, eroding consumer trust and demand for irrigation technologies. Additionally, limited access to market information and financial constraints, including foreign currency shortages, further hindered suppliers’ ambitions to increase the scale of their operations. More importantly, lengthy import processes and inefficient tax exemption systems increase equipment costs, impeding the adoption and dissemination of technologies, such as solar-powered irrigation pumps. Addressing these challenges is critical for improving the supply and effectiveness of irrigation technology in Ethiopia.